2021
DOI: 10.1038/s41467-020-20274-1
|View full text |Cite
|
Sign up to set email alerts
|

Unified divergent strategy towards the total synthesis of the three sub-classes of hasubanan alkaloids

Abstract: Elegant asymmetric synthesis of hasubanan alkaloids have been developed over the past decades. However, a divergent approach leading to all three sub-classes of this family of natural products remains unknown. We report herein the realization of such an endeavor by accomplishing enantioselective total syntheses of four representative members. The synthesis is characterized by catalytic enantioselective construction of the tricyclic compounds from which three different intramolecular C-N bond forming processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Iodide 13 (three steps from ethyl 2-butynoate) represents a previously unknown but valuable alternative to the classical Stork–Jung vinylsilane . Treating a mixture of 14 and phenyl bistriflimide (PhNTf 2 ) with potassium hexamethyldisilazide (KHMDS) gave the corresponding enol triflate in excellent yield (85%).…”
Section: Resultsmentioning
confidence: 99%
“…Iodide 13 (three steps from ethyl 2-butynoate) represents a previously unknown but valuable alternative to the classical Stork–Jung vinylsilane . Treating a mixture of 14 and phenyl bistriflimide (PhNTf 2 ) with potassium hexamethyldisilazide (KHMDS) gave the corresponding enol triflate in excellent yield (85%).…”
Section: Resultsmentioning
confidence: 99%
“…Structurally, this class of natural products, sharing a common aza[4.4.3]­propellane core, differs mainly on the oxidation level of the polycyclic structure and the presence of an additional oxa-heterocycle. While the total synthesis campaign started in the late 1960s, asymmetric syntheses have been accomplished only recently. …”
mentioning
confidence: 99%
“…More than 40 congeners of these alkaloids have been identified to date, and they show a wide range of biological activities, including antiviral, antimicrobial, and cytotoxic activities . Hasubanan alkaloids, exemplified by compounds 2 – 5 , commonly possess a characteristic tetracyclic aza­[4,4,3]­propellane core 1 (Figure a). , Owing to the synthetically challenging structures of these alkaloids as well as their important biological activities, numerous synthetic studies have been reported. …”
mentioning
confidence: 99%